DEVELOP SOCIAL EMOTIONAL IN RECOGNIZING COLORS USING EXPERIMENTAL METHODS WITH EXTRATION MODELS IN GROUP B - Sekar Oktaviani Dwi Susanti; Faqihatuddiniyah Faqihatuddiniyah (E-CHIEF Journal, 2023)
The problem in this study is that the children are not independent and impatient in studying Group B in Aisyiyah Busthanul Athafal 36 Kindergarten Banjarmasin. Learning activities are a crucial factor in the success of the learning process carried out through the activities of the teachers. The activity of teachers is the main factor in various achievements, especially in children's learning activities, which affect the success of children's developmental outcomes. However, business and development results are still relatively low. Therefore, the purpose of data collection is to determine the increase in children's developmental activity and outcomes using a combination of extraction models. The type of research used is Classroom Action Research (CAR) which took place with 4 meetings. The research subjects were children of Group B of Aisyiyah Busthanul Athfal 36 Kindergarten Banjarmasin in school year 2021/2022. The results showed that the activity of the teacher at the first meeting was quite good, the second and third meetings in the category of good, the fourth meeting was very good. Student activity at the first meeting met the criteria of being less active, the second met the criteria of being reasonably active, the third met the criteria of being active, and the fourth met the criteria of being very active. The classic completeness of child development outcomes was 30% at the first meeting, 50% at the second meeting, 90% at the third meeting, and 100% at the fourth meeting. Based on these results, it can be concluded that the combination of explicit instructions and demonstration models can improve the outcomes of the activities and the child's development. It is recommended to use this model as an alternative to reinforce the activities of the teacher and the child that have an impact on improving the child's developmental outcomes.